Pengaruh Bahan Peremaja Terhadap Sifat Penuaan Aspal - Laksmi, Nadia Novita; , Ir. Sri Sunarjono, MT,.PhD; , Ir. Agus Riyanto, MT (2016)
Road pavement is one of the most important things to support transportation continuity.Seeing an increase in the mobility populationis very high, so it is necessary to improve the quality of the road transportation infrastructure development which is eco-friendly, cheap and long lasting byinnovation of aged asphalt rejuvenation. One of the ways this rejuvenation method by rejuvenateaged asphalt use rejuvenating agents i.e. cooking oil, kerosene, diesel and virgin asphalt.The purpose or objective of this research is to find out the characteristics of the aged asphalt, aged asphalt with rejuvenation agents , and analyze of rejuvenation agents effect in improve aged asphalt characteristic. This research uses experiment method by variaton of rejuvenating agents additional 0%, 2%, 4%, 6% against total weight of asphalt to know the effect of rejuvenating agent additional in improve asphalt characteristic. For long term aging test (Long Oven Aging Tram, LTOA) should oven the asphalt at temperature of 85 ˚ C for approximately 5 days. Then conducted the testing of asphalt and asphalt addedrejuvenation penetration test, specific gravity test, softening point test, flash and fire point, viscosity test, ductility test, and asphalt weight loss due to high temperature. After conducted research, the results are put in the penetration index data and prediction of stiffness (rigidity of asphalt) Based on the research of the effect of rejuvenating agents on the asphaltaging properties, its results were very influential in restoring the proportion of asphalt which have got aging. It is evidenced by the results of after addition of rejuvenating agents getting increase or approaching specification of virgin asphalt.Based on the addition of rejuvenating agents is obtained summary that the best rejuvenating agent is cooking oil, can be seen from the results more approaching specification of Bina Marga 2010 Division 6 Revision 3, the result that qualified are:Softening point use variation of 2%-6% result is decrease,Flash point of 2%- 6% result is decrease, Fire point of 2% - 6% result is decrease, Ductility of2% - 6% result is increase, Viscosity of 2% - 6% result is increase, Specific gravity of 2% - 6%result is increase, weight lossdue to high temperature 2% - 4% result is increase.For variation of rejuvenation result 0%, 2%, 4%, 6% is obtained the result of additional variation of the best rejuvenating agents on asphalt characteristic improving isa mixture of 3% solar, 2.9%kerosene, 4.6% cooking oil and 5.75% virgin asphalt 5.75% against the total weight of asphalt which is used.